The botany of mangroves - Tomlinson, P.B.
Mangrove plants are encountered almost inadvertently by visitors to the tropics because they occupy all but the most exposed or rockiest shorelines. In sheltered estuaries and lagoons they are usually extensive and may even fonn a community (manga!)up to severa! kilometers wide with a gradual transition to terrestrial vegetation. Early travelers certainly were familiar with them, but avoided them because they had an unwholesome rcputation . They were tropical swamps, therefore mosquito and fever-ridden, that harbored unpleasant animals (notably crocodiles)and were difficult to traverse on foot. People entered to gather wood or to fish , but lived only at the edge of the swamp. Most of the dangers of the manga! are imaginary, however, and the modern tropical ecologist finds it intriguing because it represents an interphase between two contrasting types of community: terrestrial, as represented by lowland forests of varying kinds; and marine. as represented by distinctive littoral ecosystems, notably seagrass meadows and coral reefs . There is an abrupt transition frommangal to marine communities, but transitions to terrestrial communities, such as fresh-water swamps, are gradual.
Keywords: MANGROVE PLANTS; MANGROVE SWAMP ECOLOGY